The family, the market or the state? intergenerational support under pressure in ageing societies - De Santis, Gustavo (International Studies in Population, 2012)
This book touches upon a few of the major challenges that all modern societies will have to face in the near future: how to set up a resilient pay-as-you-go pension system; whether the current balance between expenses and revenues in social expenditure is viable in the future, and, if not, what changes need to be introduced; whether the relative well-being of the current and future cohorts of the old will be preserved, and how their standards of living compare to those experienced by the old in the recent past. At the micro level, the exchanges between generations are presented and discussed in detail: how they have evolved in the recent past in terms of time, money, co-residence and proximity, and what will likely happen next. The geographical scope is on Europe, Canada and South Korea. A rich documentation of tables and graphs supports the scientific analyses and the policy implications in each of the nine chapters of this book, where demography, sociology, and economics intersect fruitfully, both at the macro and at the micro level.